2000
DOI: 10.1016/s0014-5793(99)01742-1
|View full text |Cite
|
Sign up to set email alerts
|

The two dimeric forms of RNase A

Abstract: In 1965 Fruchter and Crestfield (J. Biol. Chem. 240, 2868^3874) observed that dimeric RNase A prepared by lyophilization from acetic acid could be separated into two forms. Surprisingly, no other structural or functional differences could be detected between the two forms. In 1998 a structure for dimeric RNase A was determined by X-ray crystallography by Liu et al. (Proc. Natl. Acad. Sci. USA 95, 3437^3442). We found that the two forms of dimeric RNase A have indeed different structural and functional properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 24 publications
4
36
1
Order By: Relevance
“…These signals can reasonably be attributed to the phenolic rings of tyrosine residues (Simons and Blout 1968;Grandi et al 1979). It has already been reported (Sorrentino et al 2000) that in going from the monomer to the minor and to the major dimer, the CD signals become more positive at 242 nm, and less negative at 278 nm. This finding has been reported as being the evidence of a progressively higher exposure of the phenolic rings of tyrosine residues (Grandi et al 1979).…”
Section: Circular Dichroism Analysesmentioning
confidence: 80%
See 1 more Smart Citation
“…These signals can reasonably be attributed to the phenolic rings of tyrosine residues (Simons and Blout 1968;Grandi et al 1979). It has already been reported (Sorrentino et al 2000) that in going from the monomer to the minor and to the major dimer, the CD signals become more positive at 242 nm, and less negative at 278 nm. This finding has been reported as being the evidence of a progressively higher exposure of the phenolic rings of tyrosine residues (Grandi et al 1979).…”
Section: Circular Dichroism Analysesmentioning
confidence: 80%
“…The area of each peak was measured and expressed as a percentage of the area of the corresponding input (trimers or tetramers at zero time). The results were (1) that both more basic conformers (T 2 and TT 2 ) are more labile than their less basic counterparts, a property also shared by dimeric RNase A (Sorrentino et al 2000), and (2) that both trimers are remarkably more resistant than the two tetramers. In fact, although after 2 h at 35°C about 40% of TT 1 and 60% of TT 2 were already dissociated, almost no dissociation could be detected for both T 1 and T 2 .…”
Section: Kinetics Of Thermal Dissociation Of Trimeric and Tetrameric mentioning
confidence: 99%
“…Accordingly, the latter shows in vitro a lower antitumor activity than that displayed by the CNC-tetramer. However, it has to be taken into account that, although, as mentioned above, under all experimental conditions tested the stability of the RNase A oligomers undoubtedly decreases in going from dimers to tetramers, for each oligomeric species the stability of one of the two conformers relative to that of the other appears to be greatly influenced by the environmental conditions (3,49). 2 In conclusion, however, the activity patterns shown in Figs.…”
Section: Mice Embryos After 72 Hours Incubation With Rnase a Oligomermentioning
confidence: 81%
“…Another point to be considered in relation to the biological activities reported here is the survival of the various RNase A oligomers in solution and in in vitro or in vivo experiments. The stability of dimers, trimers and tetramers, dissolved in different buffers at neutral pH, was studied as a function of temperature, and the kinetics of the dissociation of trimers and tetramers at 35°C was measured (3,49). The results consistently indicated that dimers are relatively more stable than trimers and tetramers, the latter being the least stable oligomers.…”
Section: Mice Embryos After 72 Hours Incubation With Rnase a Oligomermentioning
confidence: 96%
“…Beside BS-RNase, other ribonucleases, such as RNase A (25,26) and human pancreatic ribonuclease (HP-RNase) (27), are able to form in vitro non-covalent dimers through the swapping of a structural element among subunits. In particular, under well defined experimental conditions, monomeric RNase A produces two different non-covalent dimeric forms (26), both studied crystallographically: ND-RNase A, where the N-terminal ␣-helices are interchanged (28) and CD-RNase A, where the swapping involves the C-terminal ␤-strands (29).…”
mentioning
confidence: 99%